Maniçobeira (Manihot cf. pseudoglaziovii Pax & K. Hoffm.): utilização e importância para a agricultura familiar em Santo Antonio do Tauá, Pará - NEGRÃO, Bruna Luiza Ciarini (2019)
In the Amazon region, family farming is more characteristic than in other regions, predominating the extraction of natural resources and much of food production. This paper aims to analyze the production of maniçobeira and its social, cultural and economic relationship with family farmers of the Association of Residents and Producers of Traquateua - AMPTEUA, to describe the production chain of the maniçobeira family farmers of Santa Maria do Ubintuba Community in the municipality. Santo Antônio do Tauá, in addition to conducting a Community diagnosis for maniçoba production stations, processing and processing for the precooked manioc. The methods used in this research were the use of questionnaires, construction of location maps, collection of leaves of Maniçobeira and evaluation of dry matter in the laboratory through graph. The results show that there is still misinformation regarding the researched crop and its economic potential, even though it is a viable alternative for farmers, that is, there is a market for the commercialization of this product. supplying this trade, this problem also weakens the agro-industry that benefits the product. Thus, as a product of this research, a Primer was built that will be applied to farmers, showing them the advantages of cultivating maniçobeira, as well as an appropriate layout for the proper functioning of the agribusiness, as strategic actions to improve the production of maniva. precooked in the community, since it has long been known for its high production of maniçoba. Thus, it is clear that the pre-cooked manioc market, whether with cassava or manioc leaves, is large and compensates the producer for this type of production and even at a slow pace, the pre-cooked manioc agro-industries will adapting together with the supervisory bodies and building a dynamic of this in an appropriate way for the later agribusinesses that arise.